2021
DOI: 10.1071/fp21161
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles (AgNPs) internalization and passage through the Lactuca sativa (Asteraceae) outer cell wall

Abstract: Silver nanoparticle (AgNPs) toxicity is related to nanoparticle interaction with the cell wall of microorganisms and plants. This interaction alters cell wall conformation with increased reactive oxygen species (ROS) in the cell. With the increase of ROS in the cell, the dissolution of zero silver (Ag0) to ionic silver (Ag+) occurs, which is a strong oxidant agent to the cellular wall. AgNP interaction was evaluated by transmission electron microscopy (TEM) on Lactuca sativa roots, and the mechanism of passage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…For example, some nanomaterials may potentially trigger pore enlargement because the plant cell wall is a dynamic structure and has the flexibility to undergo rapid remodeling in response to changes in the surrounding environment ( Houston et al., 2016 ). A previous study has shown that with shifting of Ag 0 to Ag + in AgNPs, which interact with ROS (reactive oxygen species), the released Ag + can bind to hydroxyls in the cellulose structure, causing the breakdown of hydrogen bonds to facilitate changes in cell wall structure that allow passage of AgNPs ( Kennedy et al., 2021 ). The cell wall also has an electrochemical gradient that may favor differently charged NPs.…”
Section: From the Outside To The Inside Of A Cell: How Do Nps Travel ...mentioning
confidence: 99%
“…For example, some nanomaterials may potentially trigger pore enlargement because the plant cell wall is a dynamic structure and has the flexibility to undergo rapid remodeling in response to changes in the surrounding environment ( Houston et al., 2016 ). A previous study has shown that with shifting of Ag 0 to Ag + in AgNPs, which interact with ROS (reactive oxygen species), the released Ag + can bind to hydroxyls in the cellulose structure, causing the breakdown of hydrogen bonds to facilitate changes in cell wall structure that allow passage of AgNPs ( Kennedy et al., 2021 ). The cell wall also has an electrochemical gradient that may favor differently charged NPs.…”
Section: From the Outside To The Inside Of A Cell: How Do Nps Travel ...mentioning
confidence: 99%
“…For example, yttrium oxide nanoparticles caused local thickening of cell wall, in which pectin content increased by 58% and hemicellulose content decreased by 29% . AgNPs bind to hydroxyl groups in cellulose, leading to hydrogen bond cleavage and altering the structure of cell walls . However, there is currently no research exploring how the components of cell walls affect the uptake efficiency of NMs contrasting the zeta potential by leaf cells.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found that NMs can affect plant development by altering the physical properties of cell walls through interacting with cell walls. , AuNPs (gold nanoparticles, 5 nm, 50 μg/mL, zeta potential value not reported) affect the presence and distribution of pectin and arabinogalactan protein epitopes in the root cells walls . Nanoparticles can also cause remodeling of plant cell wall, including the changes in lignin, pectin, and other components in cell wall. , AgNPs (silver nanoparticles, 15 nm, 40.8 mV, 100 mg/L) can alter the conformation of cellulose by binding to the hydroxyl group of cellulose in the cell wall, leading to hydrogen bond cleavage and altering the structure of cell walls, thus affecting the shuttling efficiency of AgNPs . Zero-valent iron (0.5 g/L, size and zeta potential value not reported) induces pectin degradation in the cell wall of Arabidopsis , causing the loosening of cell wall .…”
mentioning
confidence: 99%
“…Pesticide nanocarriers are expected to grow rapidly in the coming years. , However, the use of nanoenabled agrochemical products will inevitably release them into the environment, which can potentially impact nontarget organisms. The discovery and development of nanoenabled products depend heavily on studies about the effects of nanoformulations, such as nanopesticides and nanobiopesticides, on agricultural soils. Understanding the environmental fate and behavior of nanoenabled products in soil systems is required to promote the development of safe-by-design nanopesticides.…”
Section: Introductionmentioning
confidence: 99%